2012
DOI: 10.1523/jneurosci.5083-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Neural Activity in Cortical Area V4 Underlies Fine Disparity Discrimination

Abstract: Primates are capable of discriminating depth with remarkable precision using binocular disparity. Neurons in area V4 are selective for relative disparity, which is the crucial visual cue for discrimination of fine disparity. Here, we investigated the contribution of V4 neurons to fine disparity discrimination. Monkeys discriminated whether the center disk of a dynamic random-dot stereogram was in front of or behind its surrounding annulus. We first behaviorally tested the reference frame of the disparity repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
74
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 49 publications
12
74
1
Order By: Relevance
“…Although it might be surprising to some readers, this observation is consistent with studies that involve fine discrimination tasks in other sensory systems, where perceptual threshold may be set by the most sensitive neurons available (4). For example, similar findings have been reported for orientation discrimination in primary visual cortex (V1) (31), fine direction discrimination in the middle temporal (MT) visual area (7), and fine binocular disparity discrimination in areas V4 (32) and V1 (33). In contrast, studies that have compared neuronal and psychophysical performance in coarse discrimination or amplitude discrimination tasks have often reported that many single neurons are more sensitive than the animal (5, 6, 9, but also ref.…”
Section: Discussionsupporting
confidence: 74%
“…Although it might be surprising to some readers, this observation is consistent with studies that involve fine discrimination tasks in other sensory systems, where perceptual threshold may be set by the most sensitive neurons available (4). For example, similar findings have been reported for orientation discrimination in primary visual cortex (V1) (31), fine direction discrimination in the middle temporal (MT) visual area (7), and fine binocular disparity discrimination in areas V4 (32) and V1 (33). In contrast, studies that have compared neuronal and psychophysical performance in coarse discrimination or amplitude discrimination tasks have often reported that many single neurons are more sensitive than the animal (5, 6, 9, but also ref.…”
Section: Discussionsupporting
confidence: 74%
“…This was further evidenced by the findings from a study by Shiozaki et al [67], in which the authors examined how V4 activity relates to behaviour in a fine disparity discrimination task, which was based on relative rather than absolute disparity signals. They found that the information encoded by V4 neurons was nearly sufficient to support behaviour during relativedepth discrimination.…”
Section: Disparity Processing In the Mid-stages Of The Ventral Visualmentioning
confidence: 90%
“…The chance-level performance is 50%, and a correct performance rate below 50% indicates reversed depth. We assumed a readout mechanism suitable for near/far discrimination; the sensory outputs of the matching or correlation computations are compared between their near and far detectors, and whichever detector has the larger response determines the choice [23][24][25]36]. Through this readout mechanism, the correlation computation predicts that a negative correlation between the paired images leads to reversed depth perception because the response balance is reversed between near and far detectors.…”
Section: Reversed Depth In Anti-correlated Random-dot Stereogramsmentioning
confidence: 99%
“…Monkeys are a useful model animal to study stereoscopic depth perception because they perceive depth in a similar way to humans [7,8,36,53]. Classically, the neural processing of binocular disparity was ascribed to the dorsal (occipitoparietal) pathways [54,55].…”
Section: Neural Mechanism Of the Correlation And Matching Representatmentioning
confidence: 99%